Efeito da alimentação do adulto na qualidade do endoparasitoide larval da broca comum da cana-de-açúcar - Bortoli, Sergio Antonio de [UNESP]; Viel, Silvio Rogerio [UNESP]; Vacari, Alessandra Marieli [UNESP]; De Bortoli, Caroline Placidi [UNESP]; Santos, Rafael Ferreira dos [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2015)
Aiming qualitative improvements in the mass rearing of Cotesia flavipes (Cameron, 1891) (Hymenoptera: Braconidae) in laboratory, tests were conducted with adults feed before parasitism on Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Crambidae) larvae, using 14 artificial diets based on sucrose, brewer yeast and honey. The design was completely randomized with 15 treatments and five replications. The biological parameters evaluated in F1 and F2 generations were: number of adults emerged; sex ratio; adult emergence percentage; weight of pupae mass; and male and female longevity. The highest average of emerged adults were 85 in diet with sucrose 5% for F1 generation, and 91 in diet with sucrose 5% + yeast brewer 2,5% for F2; the smaller average of adult emergency were 63.60 in diet with honey 5% + yeast brewer 2.5 % for F1 generation and 66.80 in diet with honey 5% for F2. Diets that produced more females were honey 5% + yeast brewer 2.5%, showing the sex ratio of 0.82 for F1 generation, and sucrose 10% + 2.5% yeast brewer 2.5% (0.75) for F2, while sucrose 10% + yeast brewer 2.5% (0.60 for F1) and honey 2.5% (0.59) provided fewer females for F2 generation. The highest percentage of adult emergence were 93.90% with the diet containing sucrose 2.5% + yeast brewer 2.5%) and 93.89 % with honey 5% + yeast brewer 2.5%, and the lowest 81.71% (honey 5% + yeast brewer 2.5%) for F1 and 78.96 % (honey 5%) to F1 and F2, respectively. The diet with Mel 2.5% produced greater weight of pupae mass. The adult longevity did not differ significantly for all diets in F1 and F2 generations. Diets containing 5% or 10% of sucrose or honey provide, in general, improve the qualitative development of C. flavipes in mass rearing.

Visando melhorias qualitativas na criação de Cotesia flavipes (Cameron, 1891) (Hymenoptera: Braconidae) em laboratório foram realizados testes com alimentação de adultos antes do parasitismo em Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Crambidae), utilizando 14 dietas a base de sacarose, lêvedo e mel. Foram avaliados: adultos emergidos; razão sexual; porcentagem de emergência; peso das massas de pupas; e longevidade dos adultos nas gerações F1 e F2. O delineamento foi inteiramente casualizado, com 15 tratamentos e 5 repetições. As maiores médias de adultos emergidos foram 85 (5% sacarose) em F1 e 91 (5% sacarose + 2,5% lêvedo) em F2 e as menores 63,60 (5% mel + 2,5% lêvedo) em F1 e 66,80 (5% mel) em F2. As dietas que proporcionaram mais fêmeas foram 5% mel + 2,5% lêvedo (0,82) em F1 e 10% sacarose + 2,5% lêvedo (0,75) em F2, sendo menos para 10% sacarose + 2,5% lêvedo (0,60) em F1 e 2,5% mel (0,59) em F2. As maiores porcentagens de emergência foram 93,90% (2,5% sacarose + 2,5% lêvedo) em F1 e 93,89% (5% mel + 2,5% lêvedo) em F2 e as menores 81,71% (5% mel + 2,5% lêvedo) para F1 e 78,96% (5% mel) em F2. O mel (2,5%) levou a um maior peso de massas. A longevidade não diferiu significativamente para as dietas nas gerações F1 e F2. E as dietas contendo 5% ou 10% de sacarose ou mel proporcionaram, no geral, melhoria qualitativa no desenvolvimento de C. flavipes em criações massais.
Effect of adulto feeding on the quality of sugarcabe borer larvae endoparasitoid
Keywords: Biological control; Cotesia flavipes; Mass rearing; Diatraea saccharalis; Nutrition